THE ROLE OF STUDENT ORGANIZATIONS IN THE DEVELOPMENT OF MANAGERIAL SKILLS AMONG STUDENTS AT THE FACULTY OF ECONOMICS AND BUSINESS, MAKASSAR STATE UNIVERSITY - Uhud Darmawan Natsir (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The objective of this research is to determine the role of student organizations in enhancing the managerial skills of students at the Faculty of Economics and Business, Makassar State University. This research is a qualitative study with a case study approach. This research is geographically located in the Gunungsari village, Rappocini district, Makassar City, specifically at the Faculty of Economics and Business, Makassar State University, the higher education institution where the researcher is pursuing their studies. This research began in February-March 2024. The data obtained through interviews with 13 informants were divided into three categories: key informants, expert informants, and additional informants. Next, the collected data were analyzed using the source triangulation method. The research results show that student organizations play a role in the development of students' managerial skills. Operational activities within student organizations indirectly develop students' managerial skills in terms of conceptual, interpersonal, and technical aspects.